2019
DOI: 10.1186/s40851-019-0126-2
|View full text |Cite
|
Sign up to set email alerts
|

Etmopteridae bioluminescence: dorsal pattern specificity and aposematic use

Abstract: Background In the darkness of the ocean, an impressive number of taxa have evolved the capability to emit light. Many mesopelagic organisms emit a dim ventral glow that matches with the residual environmental light in order to camouflage themselves (counterillumination function). Sharks use their luminescence mainly for this purpose. Specific lateral marks have been observed in Etmopteridae sharks (one of the two known luminous shark families) suggesting an inter/intraspecific recognition. Convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…It is possible that modified harvesting and curing regimes may lessen the negative impact of this allelic variability on cured leaf quality in low nicotine materials. It may also be important to study the potential for increased insect herbivory on tobacco plants with reduced nicotine accumulation, as increased insect feeding has been observed on Nicotiana plants with silenced nicotine biosynthetic genes (Steppuhn et al, 2004). Nolke et al (2018) reported increases in polyamine content to be correlated with delays in maturation and senescence in a study of nic1/nic2 isolines of burley tobacco, with problems being most apparent in the lowest alkaloid material.…”
Section: Combining Bbl Mutations With Recessive Alleles At the Nic1 Amentioning
confidence: 99%
“…It is possible that modified harvesting and curing regimes may lessen the negative impact of this allelic variability on cured leaf quality in low nicotine materials. It may also be important to study the potential for increased insect herbivory on tobacco plants with reduced nicotine accumulation, as increased insect feeding has been observed on Nicotiana plants with silenced nicotine biosynthetic genes (Steppuhn et al, 2004). Nolke et al (2018) reported increases in polyamine content to be correlated with delays in maturation and senescence in a study of nic1/nic2 isolines of burley tobacco, with problems being most apparent in the lowest alkaloid material.…”
Section: Combining Bbl Mutations With Recessive Alleles At the Nic1 Amentioning
confidence: 99%
“…Lantern sharks, i.e., Etmopteridae, constitute a conspicuous group of small‐sized elasmobranchs that have the capability of emitting light (bioluminescence) from tiny luminous organs on their ventral epidermis (Duchatelet et al, 2019). Etmopteridae currently includes 51 valid species and is the most speciose family of Squaliformes (Fricke et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…They display thousands of tiny organs, photophores, that emit blue-green light ( Fig. 1a-d) [47][48][49] . Among Etmopteridae, the velvet belly lanternshark, Etmopterus spinax is the most studied lanternshark.…”
mentioning
confidence: 99%